WANITA DAN UNDANG-UNDANG (Perspektif Undang-Undang Harta dan Muamalat di Malaysia)* - Siti Mashitoh Mahamood (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
This writing will discuss the problem of women and law thatfocus on anything related with the regulation of treasure andmuamalat in Malaysia nowadays. But this writing will not discussit in detail because of some limitations. Therefore, the writer willonly talk about very important and urgent things to discuss byreferring to the regulation in Malaysia, both Islamic law andconventional regulation.